Extracts of Apium graveolens (Celery) attenuate hepato-renal injury induced by chronic administration of gentamicin in mice through activation of Nrf2-antioxidant signaling pathways - Arnaud Kouam; Mayelle Mokam; Eleonore Ngounou; Ferdinand Kouoh; Rodrigue Fifen; Kerinyuy Kongnyuy; Elisabeth Zeuko’o; Nembu Nembo; Pascal Dieudonné Djamen; Frédéric Njayou; Paul Moundipa; Emmanuel Asongalem (Avicenna Journal of Phytomedicine)
Objective: This study aimed at investigating the protective effect of extracts from Apium graveolens against gentamicin-induced hepato-renal toxicity.Materials and Methods: The aqueous and hydro-ethanolic extracts of A. graveolens designated respectively as WAG and HAG were tested for their in vitro antioxidant activities. Then, their cytoprotective effects were assessed against gentamicin-induced cytotoxicity in primary mouse hepatocytes. Finally, mice were administered with gentamicin (20 mg/kg) and co-treated with HAG for 14 days, and histopathology, biochemical and molecular parameters related to gentamicin-induced toxicity were evaluated.Results: HAG exhibited outstanding chemical antioxidant activities and preserved hepatocytes from gentamicin-induced cytotoxicity.  HAG relieved liver and kidney histopathological and biochemical changes, and enhanced the mRNA level of Nrf2 and its target gene HO-1 in gentamicin-intoxicated mice.Conclusion: HAG attenuates hepato-renal injuries induced by 14-days administration of gentamicin in mice through the activation of Nrf2-antioxidant signaling pathways.